2017
DOI: 10.5194/acp-2017-769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological transformation of soot: investigation of microphysical processes during the condensation of sulfuric acid and limonene ozonolysis product vapors

Abstract: Highlights:1. Morphological transformation occurs via two key complementary and sequential processes, i.e., void filling in the particle and its diameter growth 15 2. A framework was developed for quantifying the state of morphological transformation of soot, i.e., the utilization of material for filling and growth during the condensation processes 3. A method was developed for (i) quantifying the fraction of internal voids and open voids in the soot agglomerate, (ii) deriving the volume equivalent diameter (i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Our rationale for using a fixed refractive index is to isolate how the changes in the aerosol size and number affect extinction. The particle extinction is also a function of potentially evolving particle morphology and refractive index in the plume during aging (Pei et al, ), but we do not attempt to address these changes here with justification given in the next paragraph.…”
Section: Methodsmentioning
confidence: 99%
“…Our rationale for using a fixed refractive index is to isolate how the changes in the aerosol size and number affect extinction. The particle extinction is also a function of potentially evolving particle morphology and refractive index in the plume during aging (Pei et al, ), but we do not attempt to address these changes here with justification given in the next paragraph.…”
Section: Methodsmentioning
confidence: 99%
“…The rapid-transition model is further motivated by recent laboratory measurements reported in [31], where the morphological changes of soot particles during the process of condensation of coating material are investigated. They observed that a gradual increase of the amount of coating material first had a negligible effect on the particles' mobility diameter, followed by a sudden sharp increase in diameter.…”
Section: Particle Modelsmentioning
confidence: 99%
“…2. The coating mechanism is attributed to two pathways, including the direct condensation of supersaturated H2SO4 vapor and the adsorption of small H2SO4 particles formed by homogeneous nucleation (Bambha et al, 2013;Pei et al, 2018). The aerosol sample flow used to generate H2SO4 vapor is heated in an aluminium heating block before going through a flask containing 50 ml pure H2SO4 (Sigma-Aldrich, 95.0-97.0 %) mounted on another aluminium heating block.…”
Section: Coating Apparatusmentioning
confidence: 99%
“…For example, fractal soot agglomerates can be compacted by the condensation of ozonolysis products of α-pinene secondary organic aerosol (SOA) with the bare soot particle serving as a nucleation centre (Saathoff et al, 2003). Khalizov et al (2009) also pointed out that small soot-aggregates gain size growth but larger aggregates show a dramatic size shrinkage due to structure compaction after being exposed to gaseous H2SO4 for more than 10 s. Most recently, Pei et al (2018) investigated the morphological changes of soot particles after H2SO4 or limonene ozonolysis SOA coating, and suggested that the coating material will change soot particle nanostructure by a two-step process. Firstly, external coating material will fill into the voids or pores among soot-aggregates.…”
Section: A Three-step Process For Soot Particle H2so4 Coatingmentioning
confidence: 99%
See 1 more Smart Citation